Faktor-Faktor yang Mencirikan Kondisi Financial Distress Pasca Kenaikan BBM Perusahaan Manufaktur di BEI Menggunakan Analisis Biplot - Venny Oktarinda; Syafriandi Syafriandi; Nonong Amalita (Journal of Mathematics UNP, 2014)
Abstract Financial distress is  situation where financial condition  company in crisis. Prices increasis BBM is one of the external factors cause occurrence of financial distress. So that company can overcome problem of financial distress, it’s necessary know factors that characterize financial condition by financial ratios of manufacturing companies on Indonesian  Stock  Exchange before and after increase  prices BBM using biplot analysis. Biplot results indicate that factors characterize company condition good company prior to the rise in fuel prices is value of CR, DER, and ROE above average and value TATO is below average. After the occurrence of  condition of  fuel price hike company declined to cash flow problems and deterioration. Company's cash flow problems on condition characterized by value of CR above average and of DER, TATO, and ROE is below average. Company on condition characterized by deterioration DER values ​​were above average, value CR, TATO, and ROE is below average.   Keywords financial distress, financial ratios, biplot analysis